Pengembangan Media Gamifikasi untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas V Sekolah Dasar - Twiningsih, Anik (Jurnal Didaktika Pendidikan Dasar, 2024)
The development of gamification media is currently still not widely developed by teachers, especially in elementary school learning. The purpose of this study is to describe the results of the development of gamification media products to improve the mathematics learning outcomes of elementary school students. The research and development method used is the Borg and Gall research method with 5 stages, namely needs analysis, data collection, product development, product validation, and product revision. This research resulted in a product for the development of gamification media for mathematics learning in grade 5 elementary school. The validation results of 3 validators showed that the results of the validation percentage of media experts were 94%, the results of the validation percentage of material experts were 94%, and the results of the validation percentage of linguists were 90%. From the validation results of the three validators, it was concluded that the gamification media development product was feasible to use, because it was in accordance with the criteria was very feasible. So it can be concluded that gamification media is worthy of being tested in learning to improve the mathematics learning outcomes of elementary school students.